Caracterización de valores hemáticos (biometría hemática) en el cuy (Cavia porcellus) en la Provincia de Cotopaxi Cantón Salcedo en las parroquias Cusubamba y San Miguel - Laguaquiza Llanganate, Walter Rolando (2015)
This research was conducted in Cusubamba and San Miguel Parishes, located in Salcedo Canton, Cotopaxi Province. The aim of the research was to characterize hematologic values in guinea pigs (Cavia porcellus) 100 animals divided into two groups were selected. Group No.1 Cusubamba and group No. 2 San Miguel, the objective of the research was to check for changes in blood components by geographic location. The Cusubamba parish is 3,583 meters and San Miguel parish is 2,628 m, the cardiac puncture technique depositing the samples used in tubes with anticoagulant allowing blood to keep transportation to the "SERVILAT" laboratory where the counting was done blood components. When testing "t" student determined that there is a minimum numerical difference between the two locations, determining which are among the established reference ranges....